Phosphorus removal in different wastewater by fluidized bed airlift reactors with internal circulation - Iván Andrés Sánchez Ortiz; Gleyce Teixeira Correia; Dib Gebara; Milton Dall’Aglio Sobrinho; Tsunao Matsumoto (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
The wastewater discharge produces impacts on receiving water bodies. Nutrients as P produce implications on lentic systems because they accelerate the eutrophication processes. Several technologies for P removal from the wastewater have been used: physic chemical treatment systems with important effects by coagulant products addition; biological processes based on anaerobic and aerobic conditions with great implications on the required volume; natural systems as stabilization ponds and irrigation require bigger areas and post-treatment processes. The aerobic fluidized bed reactors with internal circulation (AFBRIC) are compact options with high concentrations of active biomass that have demonstrated their capacity for organic matter and N removal. For sewage from the wastewater pumping station of Ilha Solteira city and effluents of a recirculation aquaculture system (RAS) for semi-intensive tilapia farming, the reactive P and total P removal efficiency in three AFBRIC with 250 mm external tube diameter and different internal tube diameter (ITD), for two different support media at different concentrations was evaluated. The average reactive P removal efficiency for domestic wastewater to hydraulic retention time (HRT) of 3 hours and 125 mm ITD reactor varied from 25,6 to 38,4% and with 150 mm ITD reactor varied from 27,5 to 32,5%; the average total P removal for the RAS wastewater at a HRT of 0,19 hours and 100 mm ITD was of 32,7%.